Financial leasing as one of the most important Islamic formulas applied in Islamic banks - berrabeh, dalal (Journal of Research in Finance and Accounting, 2022)
We tried through this research paper to shed light on financial leasing as one of the most important Islamic formulas applied in Islamic banks. After we touched on the generalities about financial leasing, by defining it and highlighting its ruling, in addition to mentioning its conditions and characteristics,We discussed its advantages and disadvantages, as for the second section, its content was about the forms of the financial leasing contract and the most important areas of its application